Abnormal Morphology of Blood Vessels in Erythematous Skin From Atopic Dermatitis Patients. (May 2016) - Tsutsumi, Moe; Fukuda, Maki; Kumamoto, Junichi; Goto, Makiko; Denda, Sumiko; Yamasaki, Kenshi; Aiba, Setsuya; Nagayama, Masaharu; Denda, Mitsuhiro
Abstract : Abstract: Previous studies suggest that altered peripheral blood circulation might be associated with erythema or inflammation in atopic dermatitis (AD) patients. However, the overall structure of blood vessels and capillaries in AD skin is poorly understood because most studies have involved light-microscopic observation of thin skin sections. In the present study, we compared the 3-dimensional structures of peripheral blood vessels of healthy subjects and AD patients in detail by means of 2-photon microscopy. In skin from healthy subjects, superficial vascular plexus and capillaries originating from flexous blood vessels were observed. However, skin from AD patients contained thickened, flexuous blood vessels, which might be associated with increased blood flow, in both erythematous and nonlesional areas. However, patients with lichenification did not display these morphological changes. Bifurcation of vessels was not observed in either erythematous or lichenification lesions. These results might be helpful for developing new clinical strategies to treat erythema in AD patients.